THE STATE-ADMINISTRATIVE TITLE “TEGIN” (TEGIN) AMONG THE YENISEI KYRGYZ (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2022)
The title “tegin” (tegin) was one of the main and important state and political positions in the Kyrgyz kaganate, the title was held by the closest relatives of the kagan, princes, i.e. tegins, commanded troops, were appointed ambassadors and performed various functions in the public service. The Yenisei script of the Kyrgyz confirms that the position (title) “tegins” belonged to the dynastic clan of the Kyrgyz kagans. The data of written sources (runic, etc.) report that the state title “tegin” was used not only by the rulers of the II Eastern Turkic Khaganate (682-744), but also by representatives of the Kyrgyz ruling elite in the VI-X centuries. In addition, the position of tegin (tegin) was one of the highest dynastic titles in the system of state-political and military administration of the ancient Xiongnu, Zhuanzhuang, Tabgaches (Wei state), Turkic Khaganates, Seyanto, Tokuz Oghuz, Yabgu state
Keywords: Kyrgyz, Tegin, Yenisei Kyrgyzes, titles, prince, kagan, runic, dynasty, etymology.